Transformation Of Rust In The Presence Of Mangrove (Rhizophoru Apiculuta)Tannins And Phosphoric Acid. - Abdul Rahim, A.; Kassim, M. Jain; Rocca, E.; Steirrmetz, J. (2009)

(untitled)
The known hazardous effects of most synthetic corrosion inhibitors are reasons to search for safer and environmentally friendly natural products. The role of mangrove (Rhizaphora apiculata) tannins and phosphoric acid as rust converters by phaser transformation studies is evaluated.